2003
DOI: 10.1097/00006324-200302000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Wavefront Aberrations of Ophthalmic Progressive-Power Lenses in Normal Viewing Conditions

Abstract: Changes in corneal optics have been measured after downward gaze. However, ocular aberrations during downward gaze have not been previously measured. A commercial Shack-Hartmann aberrometer (COAS-HD) was modified by adding a relay lens system and a rotatable beam splitter to allow on-axis aberration measurements in primary gaze and downward gaze with binocular fixation. Measurements with the modified aberrometer (COAS-HD relay system) in primary and downward gaze were validated against a conventional aberromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 30 publications
1
21
0
5
Order By: Relevance
“…[21][22][23][24][25] In relation to highorder aberrations in PPLs, some previous theoretical studies 26 concluded that the shape of the image of a point through a progressive spherical power surface may be affected by coma. 23,27 In a recent study, 28 in addition to astigmatism, we found that small amounts of coma and trefoil were also present in relevant zones of PPLs. In the same work, to obtain the final optical quality of the entire system eye with PPLs, we also demonstrated the aberration coupling between both for different zones of the lens.…”
mentioning
confidence: 60%
“…[21][22][23][24][25] In relation to highorder aberrations in PPLs, some previous theoretical studies 26 concluded that the shape of the image of a point through a progressive spherical power surface may be affected by coma. 23,27 In a recent study, 28 in addition to astigmatism, we found that small amounts of coma and trefoil were also present in relevant zones of PPLs. In the same work, to obtain the final optical quality of the entire system eye with PPLs, we also demonstrated the aberration coupling between both for different zones of the lens.…”
mentioning
confidence: 60%
“…6,7 Additional and explicit data are given to compare them with our model. All data are given for a pupil diameter of 4 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from this theoretical model are then compared with quite recent experimental data, which describe the wavefront characteristics of a PAL in a spatially resolved way. 6,7 …”
mentioning
confidence: 99%
“…As patentes obtidas, e que tivemos acesso, foram entre 1970 e 1998 em número de 17. Além dos lensômetros comuns são utilizadas alternativas como as frentes de ondas (wavefront) para ter um estudo mais acurado das aber rações astigmáticas (27) . Os estudos atuais se fazem prioritariamente so bre a superfície da lente.…”
Section: Discussionunclassified